Tradução, adaptação transcultural e validação para a língua portuguesa – brasileira do Lung Transplant Quality of Life (LT-QOL) para uso em pacientes adultos após transplante de pulmão - Rodrigues, Felipe Farah Pinheiro (2023)
INTRODUCTION: The surgical procedure of lung transplantation aims to improve the quality of life and survival of patients with advanced lung diseases. Therefore, the assessment of the health-related quality of life (HRQoL) of these patients is necessary to better understand the magnitude and persistence of post-procedure improvements. In Brazil, there is no specific instrument to assess the HRQoL of these patients, with generic tools being used. The “Lung Transplant Quality of Life” (LTQOL) is an instrument proposed in the literature as an easy-to-apply questionnaire, with specific domains for the multidimensional assessment of these patients. OBJECTIVES: Carry out the translation, cross-cultural adaptation into the Portuguese-Brazilian language and validation of the quality of life questionnaire entitled “Lung transplant quality of life” (LT-QOL). METHODS: Observational study in which the translation, cross-cultural adaptation and validation of the translated version into Brazilian Portuguese and testing of the measurement properties of the assessment instrument were carried out. The translation process was based on the guidelines of the “Guidelines for the Process of Cross-cultural Adaptation of Self-Report Measures”, as well as the guidelines recommended by the “Consensus-based Standards for the selection of health Measurement Instruments” (COSMIN). The following measurement properties were tested: internal consistency; agreement; intra-rater reliability; and convergent validity – through the application of the Short Form Health Survey (SF-36) and Saint George’s Respiratory Questionnaire (SGRQ) questionnaires compared with information from the translated version of the “LT-QOL”. RESULTS: Internal consistency and reliability were considered adequate, with Crombach’s alpha (0.86) and intraclass correlation coefficient (0.93). In the agreement analysis, the questionnaire presented EPM (4.56), considered very good. The Bland Altman technique showed low mean differences (0.8) in LTQOL scores and confidence interval (95% CI: -16.9;15.3). Concurrent validity was analyzed using the Spearman correlation test, showing excellent validity with the SF36 questionnaire and good validity with the SGRQ in the test and re-teste. CONCLUSION: The translated and cross-culturally adapted version of the LTQOL instrument into Brazilian Portuguese was validated for use in patients undergoing lung transplantation. However, we suggest further studies to adapt the validated tool to a reduced version, but with the same scope, reliability and reproducibility.